A Putative Zn2Cys6 Transcription Factor Is Associated With Isoprothiolane Resistance in Magnaporthe oryzae - Wang, Zuo-Qian; Meng, Fan-Zhu; Zhang, Ming-Ming; Yin, Liang-Fen; Yin, Wei-Xiao; Lin, Yang; Hsiang, Tom; Peng, You-Liang; Wang, Zong-Hua; Luo, Chao-Xi (Frontiers in Microbiology, 2018)
ABSTRACT Isoprothiolane (IPT), a systemic fungicide, has been applied to control rice blast since the 1970s. Although resistance to IPT has been observed, the mechanism of resistance still has not been fully elucidated. In this study, nucleotide polymorphisms were detected between two IPT-resistant mutants generated in the lab, and their parental wild type isolates using a whole-genome sequencing approach. In the genomes of the two resistant mutants, single point mutations were identified in a gene encoding a Zn2Cys6 transcription factor-like protein. Notably, either knocking out the gene or replacing the wild type allele with the mutant allele (R343W) in a wild type isolate resulted in resistance to IPT, indicating that the gene is associated with IPT resistance, and thus was designated as MoIRR (Magnaporthe oryzae isoprothiolane resistance related). Along with point mutations R343W in mutant 1a_mut, and R345C in 1c_mut, a 16 bp insertion in 6c_mut was also located in the Fungal_TF_MHR domain of MoIRR, revealing that this domain may be the core element for IPT resistance. In addition, IPT-resistant mutants and transformants showed cross-resistance with iprobenfos (IBP), which was consistent with previous observations. These results indicated that MoIRR is strongly connected to resistance to choline biosynthesis inhibitor (CBI), and further work should focus on investigating downstream effects of MoIRR.